2001
DOI: 10.1002/1097-0142(20010101)91:1<90::aid-cncr12>3.3.co;2-1
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of patients with ovarian carcinoma with pegylated liposomal doxorubicin

Abstract: Pegylated liposomal doxorubicin is an effective drug when it is given as secondary therapy to patients with EOC. Lack of bulky disease is the major predictor for a favorable response, TTF, and survival. The role of this treatment in combination with other effective drugs should be explored in both previously treated and untreated patients with ovarian carcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
13
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 0 publications
1
13
0
Order By: Relevance
“…Combining an antiangiogenic agent and chemotherapy has the potential risk of synergistic toxic effects [30,31]. In this study, toxicities were generally consistent with those that have been associated with monotherapy of trebananib, PLD, or topotecan [16,32,33]. Peripheral edema has been previously identified as a risk associated with trebananib treatment and generally manageable across studies [16,17,34,35].…”
Section: Discussionsupporting
confidence: 77%
“…Combining an antiangiogenic agent and chemotherapy has the potential risk of synergistic toxic effects [30,31]. In this study, toxicities were generally consistent with those that have been associated with monotherapy of trebananib, PLD, or topotecan [16,32,33]. Peripheral edema has been previously identified as a risk associated with trebananib treatment and generally manageable across studies [16,17,34,35].…”
Section: Discussionsupporting
confidence: 77%
“…According to previous studies, the median life expectancy is <12 months. Safra et al reported a 31% overall response rate in one phase I (N=8) and two phase II (N=44) studies on recurrent ovarian cancers salvaged with first generation pegylated liposomal doxorubicin (PLD), Doxil, with median overall survival of 15 months (Safra et al, 2001). Gordon et al reported a phase II trial on the salvage chemotherapy, with Doxil 50 mg/m 2 every 4 weeks, for 89 patients with platinum and paclitaxel-refractory epithelial ovarian cancers, and showed a response rate of 16.9%.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, PPE, which is the primary dose-limiting side effect of PLD, occurred in a lower percentage of cases with respect to what was reported by the main trials testing PLD (Gordon et al, 2000Safra et al, 2001), requiring the discontinuation of treatment in only 2.8% of cases. G3-G4 PPE, in fact, hit only 10% of patients in our series, compared with 18, 17.3 and 23% registered in the previously reported studies (Gordon et al, 2000Safra et al, 2001), respectively.…”
Section: Discussionmentioning
confidence: 67%